1978
DOI: 10.3109/17453677809005754
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetry of Plantar Flexion Strength in the Foot

Abstract: A study of plantar flexion strength and calf circumference in 30 conscripts is submitted. It showed an asymmetry of strength amounting to 6-11 per cent (95 per cent confidence limits). The right leg was significantly stronger than the left, but there was no difference in strength between the dominant and non-dominant leg. There was little correlation between circumference and strength.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

1980
1980
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 3 publications
2
19
0
Order By: Relevance
“…Sadeghi et al 9 reported gait asymmetry in some temporal and kinematic parameters in normal subjects. Asymmetry of plantar flexor strength19 and electromyographic amplitude profiles in the soleus muscle20 in favour of the dominant side were found in other studies.…”
Section: Discussionsupporting
confidence: 72%
“…Sadeghi et al 9 reported gait asymmetry in some temporal and kinematic parameters in normal subjects. Asymmetry of plantar flexor strength19 and electromyographic amplitude profiles in the soleus muscle20 in favour of the dominant side were found in other studies.…”
Section: Discussionsupporting
confidence: 72%
“…Leg dominant can be determined according to a variety of criteria, such as strength, functional use, personal preference, or performance in specific skills (Hoffman, Schrader, Applegate, & Koceja, 1998). Early studies defined leg dominance by the kicking leg, the pushing-off leg in jumping skills (Damholt & Termansen, 1978), the preferred push-off leg in long or vertical jumping, and by the one-leg vertical jump test on a platform (Vagenas & Hoshizaki, 1986). Alternatively, the single-legged hop for distance (Noyes, Barber, & Mangine, 1991) and the triple jump (Risberg et al, 1995) tests are often used for the examination of functional laterality in the lower limbs (Logerstedt et al, 2012;Risberg et al, 1995).…”
Section: Determining Leg Dominance and Quantifying Asymmetrymentioning
confidence: 99%
“…In fact, it has been shown that there is a 6% to 11% difference between the left and right ankles when testing plantar flexor strength. 24 A more recent study prospectively identified that decreased plantar flexion torque as tested on an isokinetic dynamometer (30°/s and 120°/s) with the knee extended was a discriminating factor between Belgium military recruits who developed (n = 10) and those who did not develop (n = 59) Achilles tendinopathy during 6 weeks of basic training. 79 At 30°/s and 120°/s, the uninjured group generated 17.7 and 11.1 more Nm, respectively, when compared to the group that ultimately developed Achilles tendinopathy.…”
Section: Abnormal Subtalar Range Of Motionmentioning
confidence: 99%